Dietary Sialyllactose Influences Sialic Acid Concentrations in the Prefrontal Cortex and Magnetic Resonance Imaging Measures in Corpus Callosum of Young Pigs - Mudd, Austin T. (Nutrients, 2017)
Sialic acid (SA) is a key component of gangliosides and neural cell adhesion molecules important during neurodevelopment. Human milk contains SA in the form of sialyllactose (SL) an abundant oligosaccharide. To better understand the potential role of dietary SL on neurodevelopment, the effects of varying doses of dietary SL on brain SA content and neuroimaging markers of development were assessed in a newborn piglet model. Thirty-eight male pigs were provided one of four experimental diets from 2 to 32 days of age. Diets were formulated to contain: 0 mg SL/L (CON), 130 mg SL/L (LOW), 380 mg SL/L (MOD) or 760 mg SL/L (HIGH). At 32 or 33 days of age, all pigs were subjected to magnetic resonance imaging (MRI) to assess brain development. After MRI, pig serum and brains were collected and total, free and bound SA was analyzed. Results from this study indicate dietary SL influenced (p = 0.05) bound SA in the prefrontal cortex and the ratio of free SA to bound SA in the hippocampus (p = 0.04). Diffusion tensor imaging indicated treatment effects in mean (p < 0.01), axial (p < 0.01) and radial (p = 0.01) diffusivity in the corpus callosum. Tract-based spatial statistics (TBSS) indicated differences (p < 0.05) in white matter tracts and voxel-based morphometry (VBM) indicated differences (p < 0.05) in grey matter between LOW and MOD pigs. CONT and HIGH pigs were not included in the TBSS and VBM assessments. These findings suggest the corpus callosum, prefrontal cortex and hippocampus may be differentially sensitive to dietary SL supplementation.